Melanoma-induced brain metastases. Issue 5 (May 2008) - McWilliams, Robert R; Rao, Ravi D; Buckner, Jan C; Link, Michael J; Markovic, Svetomir; Brown, Paul D
Brain metastases are a common site of metastasis from malignant melanoma, and are associated with a poor prognosis. Diagnosis of brain metastasis may also have significant implications for quality of life, and management can be difficult due to rapid progression of disease and resistance to conventional therapies. In this article, we will review the published evidence for treatment modalities for melanoma-induced brain metastases and outline future directions for research. In brief, surgical management of solitary or acutely symptomatic lesions appears to alleviate symptoms and provide the possibility of local control of disease. Stereotactic radiosurgery is an increasingly utilized technique for patients with a limited number of metastases, and presents a less invasive alternative to craniotomy. External-beam radiation alone appears effective in palliating symptoms. Chemotherapy alone is relatively ineffective, though combined chemotherapy with external-beam radiation is being investigated. Future directions include combined-modality therapy, the incorporation of novel agents, and careful consideration of the structure of clinical trials for this disease.